Supplemental methionine and stocking density affect antioxidant status, fatty acid profiles, and growth performance of broiler chickens. (23rd March 2020) - Magnuson, Andrew D; Liu, Guanchen; Sun, Tao; Tolba, Samar A; Xi, Lin; Whelan, Rose; Lei, Xin Gen
Abstract: Broilers stocked in high densities may be prone to oxidative and inflammatory insults, resulting in impaired health status, growth performance, and meat quality. This study was to determine if 30% extra supplemental dl -methionine alleviated or prevented those adverse effects of a higher stocking density in broiler chickens. A total of 560 male Cornish Cross cockerels (day old) were divided into four groups: two stocking densities (9 and 12 birds/m 2 ) and two supplementations of methionine (grower: 2.90 or 3.77 g/kg and finisher: 2.60 or 3.38 g/kg). Growth performance was recorded weekly. Blood and tissues were sampled at the end of each period. High stocking density decreased ( P < 0.05) body weight and growth performance of growers and (or) finishers. Those differences were partially attenuated by the extra methionine supplementation. The high methionine elevated ( P < 0.05) glutathione (GSH ) concentration in the thigh at both ages (> 24%). The high stocking density elevated (>28%, P < 0.05) glutathione concentration in the plasma, breast, and thigh of growers, but decreased ( P < 0.05) it in the liver of growers and thigh of finishers. Interaction effects ( P < 0.05) between dietary methionine and stocking density were found on activities of the antioxidant enzyme glutathione S-transferase in the liver of growers and breast, thigh, and adipose tissue of finishers. The interaction effect was also found on activities of glutathione peroxidase and superoxide dismutase in the thigh of growers. The extra methionine decreased ( P < 0.05) hepatic gene expression of heat shock protein 90 (18%) and thigh and breast malondialdehyde concentrations of the finishers (35%). In conclusion, the 30% extra dl -methionine supplementation was able to partially mitigate adverse effects caused by the higher stocking density and to improve the redox status of the broilers.